Peak-power control of a grid-integrated oscillating water column wave energy converter. (15th August 2016) - Henriques, J.C.C.; Gato, L.M.C.; Lemos, J.M.; Gomes, R.P.F.; Falcão, A.F.O.
Abstract: A critical characteristic of most WECs (wave energy converters) is the large peak-to-average power ratio. This poses many challenges to the design of high-efficient PTO (power take-off) systems and, even more importantly, to integrate this form of renewable energy into power grids. The OWC (oscillating water column) WECs are devices whose PTO uses an air turbine as the primary energy converter. Besides its inherent simplicity, probably the greatest advantage of OWC based WECs is the ability to control or dissipate any excess of energy available to the PTO system that may occur in medium to highly energetic sea states. The contribution of the paper is the performance assessment of a new control algorithm to operate a HSSV (high-speed stop valve) installed in series with the turbine. The goal is to perform close-to-optimal latching control of the WEC and, simultaneously, operate the HSSV to limit the energy available to the turbine/generator set. The proposed control algorithm shows large improvements in the extracted mean power while limiting the peak-to-average power ratio, thus improving the power quality delivered to the electrical grid. Tests performed in a large-scale PTO test rig validated the algorithm. Highlights: A new close-to-optimal latching control is proposed for an OWC spar-buoy A new control of the excess of energy available to the power take-off is devised Peak-to-average power ratio is limited to improve the power quality Operation of the wave energy converter under more energetic sea states is allowed The algorithm is validated in a large scale test rig